Membedah Pengaruh Review Di Media Sosial Terhadap Keputusan Pembelian Skincare Skintific - Distiana Indah Lestari; Budi Harto; Taufiq Furqon Nurhakim Nurhakim; Sulistianingsih; Heddy Setiawan; Deny Hidayatullah (KOMVERSAL, 2025)
Social media has changed people's culture and habits, as well as the way people interact and communicate with each other. In this regard, advances in information and communication technology have changed the behavior of shoppers around the world. Online shopping has become more popular than conventional shopping. However, we still lack understanding on how social media reviews influence our decision to buy skincare products. Using a survey method, this quantitative study collected data from 107 respondents who had seen Skintific product reviews on social media. The results of the analysis showed that reviews on social media have a major impact on consumers' decision to purchase products, with the factors of credibility, attractiveness, and relevance of reviews contributing to increased consumer interest and decisions. In addition, the study found that customers' positive experience with the reviewed product can increase the likelihood that they will purchase the product again. This research shows how important marketing strategies that use social media reviews are in the process of making better decisions about skincare products.